Exploring the possible mechanism of low-dose naloxone exposure improving the immune microenvironment of gastric cancer tumors - Min, Xiangzhen; Ma, Yan; Lv, Mingyue; Li, Xiaoxi; Lv, Renjun; Zhao, Xiaoyong; Leng, Yufang (Frontiers in Immunology, 2025)
IntroductionGastric cancer, one of the most common cancers of the digestive tract, has high incidence and mortality rates. Until recently, surgery has been the most effective method of treatment for gastric cancer. Surgery, however, inevitably results in dysfunction of the autonomic nervous system, entry of tumor cells into the bloodstream, and immunosuppression during the perioperative period, all of which increase the risk of complications in patients with gastric cancer. Opioid receptors play an important role in the proliferation and secretion of cytotoxic factors by immune cells. Opiate usage inhibits immune cell function, reduces the release of cytotoxic factors, and enables tumor cells to evade the immune system, thereby increasing the risk of perioperative complications. Opioid antagonists may reverse opioid-mediated immunosuppression in several ways. However, studies on the molecular biology of opioid receptor antagonists in relation to their ability to improve immune function in patients with gastric cancer are limited.MethodsWe first analyzed the cancer genome atlas stomach adenocarcinoma (TCGA-STAD) dataset to determine the correlation between changes in immune function and toll-like receptor 4 (TLR4) expression in patients with gastric cancer. A transwell co-culture system was established using CD8+T and mouse forestomach carcinoma (MFC) cells. CD8+T cells were treated with different concentrations of naloxone to determine the most effective concentration for killing the tumor cells. We then performed western blotting and quantitative realtime polymerase chain reaction to determine the expression of lymphocyte activation gene 3 (Lag3), perforin 1 (Prf1), programmed death ligand 1 (PD-1), T-cell immunoglobulin and mucin domain 3 (TIM-3), and TLR4/AKT/mTOR in CD8+ T cells. An MFC-derived allograft mouse model was used to study the in vivo changes in the immune cells. Flow cytometry, ELISA, WB, and PCR were used to examine changes in the number of immune cell populations in the spleen, secretion of cytotoxic factors by immune cells, opioid receptors, AKT/mTOR, and immune checkpoint proteins, respectively, in CD8+T cells.ResultsWe found that changes in perioperative immune function strongly correlated with TLR4 expression on the surface of immune cells in patients with gastric cancer. Low-dose naloxone (LDN) increased CD8+ T cell cytotoxicity, inhibited CD8+ T cell exhaustion, inhibited Lag3, Prf1, and Tim3 expression, and increased AKT and mTOR expression in CD8+ T cells. Opioid receptors were downregulated in CD8+ T cells following LDN administration.ConclusionLDN improved the ability of CD8+T cells to kill gastric cancer cells and reduced CD8+T cell exhaustion. The mechanism underlying these LDN-mediated phenomena may involve regulation of immune checkpoint expression in CD8+ T cells, increased cytotoxic factor secretion by CD8+ T cells via the TLR4/AKT/mTOR pathway, or regulation of expression of opioid receptors on CD8+T cells, thereby further affecting CD8+T cell exhaustion.